Performance Measurement Indicators for Farmers' Organization: A Case Study in Kedah - Mohamad Izham, Ahmad (2011)
Performance measurement is a broad and interesting topic to study, especially in agriculture sector. In Malaysia, agriculture sector have been the third source of income for the national economic growth. The agriculture sector has also been determined by government as a valued prospect and needs to be concentrated especially to organization that relates with farmers. Thus, the purpose of this research is to investigate the performance measurement indicators that can be used by Farmers Organization in order to measure it performance. This study is focused on question:”What are financial and non-financial indicators that could be used as performance measurement by Farmers Organization?” To answer the research problem, this research employs the convergent interview with the Farmers Organization in Muda Agriculture Development Authority (MADA) region. From the analysis, the result suggested that have 9 indicators classified as performance measurement indicators for Farmers Organization.